EDUCATION AND SOCIALIZATION OF PSAK 72 AND ITS AUDIT PROCEDURE IMPLICATIONS THROUGH FREE NATIONAL WEBINAR - Magdalena, Renna; Sihombing, Tanggor; Karyawati, Golrida; Risty, Illyona; Herbert, Go George; Tjahjono, Josephine Kurniawati (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
Auditing is essential in ensuring the appropriateness of financial reports, the accuracy of company operations, and compliance with applicable regulations. One of the regulations governing audit procedures is PSAK 72, which establishes the essential steps in recognizing revenue from contracts with customers. Even though it has been published since 2017, implementation of PSAK 72 is mandatory starting in 2020. To help understand the implications and application of PSAK 72, a webinar entitled